Preliminary studies on the preparation of rubber seed oil alkyds - Aigbodion A I (Indian Journal of Natural Rubber Research, 1991)
Three samples of alkyd resins having 45, 52 and 62 per cent of oil were prepared using phthalic anhydride, glycerol and rubber seed oil extracted by a screw press. Progress of the reaction was followed by measurement of the acid value of the reaction mixture at 30 min intervals. The monoglyceride formed did not make a clear solution in methanol (1:3) due to presence of impurities in the oil and the dark colour of the oil resulted in the formation of the dark coloured alkyds. Extents of esterification calculated at the time when there wasa sharp decrease in acid value were 69.92, 77.82 and 61.48 per cent for three samples. The calculated degrees of polymerization indicated formationa of appreciable high molecular weight resins. The finished alkyds were soluble in xylene (3:2 dilution). The resins were of good quality, but their properties varied with the oil content.
Keywords: Alkyd resin; Alkyd resin; Gelation; Gelation; Rubber seed oil; Rubber seed oil